Evolution of the Convective Boundary Layer in a WRF Simulation Nested Down to 100 m Resolution During a Cloud‐Free Case of LAFE, 2017 and Comparison to Observations. Issue 8 (25th April 2023) - Bauer, Hans‐Stefan; Späth, Florian; Lange, Diego; Thundathil, Rohith; Ingwersen, Joachim; Behrendt, Andreas; Wulfmeyer, Volker
Abstract: The Weather Research and Forecasting model was applied in a nested configuration from the convection‐permitting resolution of 2.5 km, via an intermediate resolution of 500 m down to the 100 m turbulence‐permitting scale to investigate the spatial and temporal evolution of the convective boundary layer and their interaction with the underlying land surface. This included detailed comparisons with observations collected during the Land‐Atmosphere Feedback Experiment, performed at the Central Facility in Oklahoma. The simulation was driven by the operational analysis of the European Center for Medium‐range Weather Forecasting for a cloud‐free case on 23 August 2017 for which the measurement operation was extended into the following night to include the evening decay of the daytime convective boundary layer. The mesoscale 2.5 km resolution was capable to represent the correct boundary layer height and its temporal evolution. Details of the morning and evening transitions between the nighttime and daytime boundary layer as well as its internal structure were only simulated by the 100 m turbulence‐permitting simulation. Although systematic differences between the simulation and lidar observations were found, the model captured the temporal and spatial structure and the statistics of turbulence rather well. Comparison with data from Eddy‐Covariance stations showed that the model was able to reproduce the evolution of many near‐surface meteorological fields. Systematically higher surface temperatures and related differences in the surface fluxes suggest weaknesses in the representation of land surface processes although the simulation was initialized with accurate and high‐resolution initial fields. Plain Language Summary: A nested configuration of the Weather Research and Forecast model was applied to simulate the evolution of the convective boundary layer for a cloud‐free case during the Land Atmosphere Feedback Experiment. The simulation was driven by the European Center for Medium‐range Weather Forecasting operational analysis and applied nests with 2, 500, 500, and 100 m resolution. Detailed comparisons with observations revealed that the applied model configuration was capable to realistically simulate the spatial and temporal evolution of the convective boundary layer including the morning transition and the evening decay. Systematic differences were an overestimated boundary layer height, weaker turbulent variability or a too weak decrease of moisture above the boundary layer, indicating that some processes may not be captured properly by the selected configuration or model physics. Comparison of higher‐order moments of water vapor mixing ratio over a three‐hour time period with lidar data revealed that the model was capable to realistically resolve the turbulence statistics, but also here systematic differences to the observations were found. Finally, comparison of surface meteorological observations with data from Eddy‐Covariance stations revealed weaknesses in the simulation of land surface atmosphere interaction. Key Points: A nested Weather Research and Forecasting simulation from 2.5 km down to 100 m horizontal resolution was set up for a cloud‐free case study during the Land‐Atmosphere Feedback Experiment experiment The turbulence‐permitting 100 m domain captured the spatial and temporal evolution of the convective boundary layer rather well Comparison with lidar data showed that the model was capable to represent the turbulence statistics although differences in detail occurred